2017
DOI: 10.1002/2017jc013097
|View full text |Cite
|
Sign up to set email alerts
|

On the Variability of the East Australian Current: Jet Structure, Meandering, and Influence on Shelf Circulation

Abstract: Given the importance of western boundary currents over a wide range of scales in the ocean, it is crucial that we understand their dynamics to accurately predict future changes. For this, we need detailed knowledge of their structure and variability. Here we investigate the jet structure of the East Australian Current (EAC), using observations from HF radars and moorings deployed at 30°S–31°S. Meandering, core velocity, width, and eddy kinetic energy (EKE) are quantified from 4 years of hourly 1.5 km resolutio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
107
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 72 publications
(113 citation statements)
references
References 55 publications
6
107
0
Order By: Relevance
“…From a global survey of mesoscale wavenumber spectra, Xu and Fu (2011) showed that the steepest slopes are over WBC regions. Increased summer EKE has been observed before in WBCs (e.g., Archer, Roughan, et al, 2017;Qiu & Chen, 2004;Ridgway & Godfrey, 1997), in phase with summer intensification of WBC jet speeds (Archer, Roughan, et al, 2017). Results from a global analysis of drifter pair separation by Corrado et al (2017) also found steep slopes down into the marginal submesoscale range (5 km).…”
Section: Discussionmentioning
confidence: 69%
See 4 more Smart Citations
“…From a global survey of mesoscale wavenumber spectra, Xu and Fu (2011) showed that the steepest slopes are over WBC regions. Increased summer EKE has been observed before in WBCs (e.g., Archer, Roughan, et al, 2017;Qiu & Chen, 2004;Ridgway & Godfrey, 1997), in phase with summer intensification of WBC jet speeds (Archer, Roughan, et al, 2017). Results from a global analysis of drifter pair separation by Corrado et al (2017) also found steep slopes down into the marginal submesoscale range (5 km).…”
Section: Discussionmentioning
confidence: 69%
“…Remote wind forcing, communicated via first mode baroclinic Rossby waves, has been shown to affect the annual cycle in volume transport (Domingues et al, 2016), but for the data presented here at 25-26°N, the Bahamas island chain blocks most of this direct mid-ocean influence (Archer, Shay, et al, 2017). At 30-31°S, the EAC has a mean core speed between 0.6 and 1.35 m s À1 (Archer, Roughan, et al, 2017;Mata et al, 2000;Schaeffer et al, 2017) and a volume transport of~22 Sv with an STD of~5-7 Sv (Mata et al, 2000;Sloyan et al, 2016). The EAC closes the South Pacific subtropical gyre, flowing poleward along SE Australia (Figure 1b).…”
Section: Introductionmentioning
confidence: 74%
See 3 more Smart Citations